Analysis of the relationship between the optimal level of public spending and economic growth Evidence and experimental study on Algeria - Mohammed BENAZZA; Djahida LAYATI (Theoretical and Applied Economics, 2025)

(untitled)
This paper discusses the optimal level of public spending in Algeria, over the period 1990-2021, employing both descriptive and quantitative methods, with a particular focus on the Autoregressive Distributed Lag (ARDL) approach and the hypotheses underlying the "Armey" curve. The findings reveal that Algeria’s public spending exceeds the level suggested by the "Armey" curve, suggesting that the country’s large government size is hindering economic growth. In other words, Algeria’s spending surpasses what is required for optimal growth, thereby obstructing economic growth.